Does genital tract GBS colonization affect the latency period in patients with preterm premature rupture of membranes not in labor prior to 34 weeks?. (March 2014) - Zilberman, Dimitry; Williams, Shauna F.; Kurian, Reah; Apuzzio, Joseph J.
Abstract Objective: To determine if genital tract colonization with GBS at the time of preterm premature rupture of membranes (PPROM) affects the latency period. Study Design: A retrospective cohort study was performed of all gravidas admitted with PPROM between 23 and 34 weeks of gestation from 1 January 2003 to 29 February 2012. Vaginal/rectal specimens for GBS were performed on admission. The latency period and infectious complications were evaluated in GBS-positive and GBS-negative groups. Results: Hundred and eighty-nine women were identified with PPROM, 177 meet the inclusion criteria. 60 patients were GBS positive on admission, 117 were GBS negative. Median latency period in GBS-positive and GBS-negative groups did not differ (6.8 versus 7.3 days, p = 0.384). Risk of intra-amniotic, wound infection, maternal and neonatal sepsis, and composite infectious morbidity did not differ between the GBS-positive and GBS-negative groups. Among patients who underwent cesarean delivery, GBS-negative group had a higher risk of endomyometritis (25%) compared to the GBS-positive group (6%), p = 0.05. Conclusion: GBS genital tract colonization on admission does not appear to affect the latency period or increase the risk of intra-amniotic infection in patients with PPROM.